Studies in development planning - Dahiya, Shri Bhagwan (Rohtak, 1997)
The present volume is another major source of reference for anyone who wants to get familiar with the economics of development issues. The book gives a broad synthetic overview of the historical contributions in the field, with a particular view on their theoretical substance. Then it moves on to a presentation of various models and methods for empirical analysis which have been developed and applied in the past decades. Finally, it takes India as a concrete study case and offers numerous scholarly insights into the reasons for and remedies against alleviation of underdevelopment in this country.
Keywords: Planning